Genetic evidence supporting the causal role of gut microbiota in chronic kidney disease and chronic systemic inflammation in CKD: a bilateral two-sample Mendelian randomization study - Ren, Feihong; Jin, Qiubai; Jin, Qi; Qian, Yiyun; Ren, Xuelei; Liu, Tongtong; Zhan, Yongli (Frontiers in Immunology, 2023)
Background The association of gut microbiota (GM) and chronic kidney disease (CKD), and the relevancy of GM and chronic systemic inflammation in CKD, were revealed on the basis of researches on gut–kidney axis in previous studies. However, their causal relationships are still unclear. Objective To uncover the causal relationships between GM and CKD, as well as all known GM from eligible statistics and chronic systemic inflammation in CKD, we performed two-sample Mendelian randomization (MR) analysis. Materials and methods We acquired the latest and most comprehensive summary statistics of genome-wide association study (GWAS) from the published materials of GWAS involving GM, CKD, estimated glomerular filtration rate (eGFR), c-reactive protein (CRP) and urine albumin creatine ratio (UACR). Subsequently, two-sample MR analysis using the inverse-variance weighted (IVW) method was used to determine the causality of exposure and outcome. Based on it, additional analysis and sensitivity analysis verified the significant results, and the possibility of reverse causality was also assessed by reverse MR analysis during this study. Results At the locus-wide significance threshold, IVW method and additional analysis suggested that the protective factors for CKD included family Lachnospiraceae (P=0.049), genus Eubacterium eligens group (P=0.002), genus Intestinimonas (P=0.009), genus Streptococcu (P=0.003) and order Desulfovibrionales (P=0.001). Simultaneously, results showed that genus LachnospiraceaeUCG010 (P=0.029) was a risk factor for CKD. Higher abundance of genus Desulfovibrio (P=0.048) was correlated with higher eGFR; higher abundance of genus Parasutterella (P=0.018) was correlated with higher UACR; higher abundance of class Negativicutes (P=0.003), genus Eisenbergiella (P=0.021), order Selenomonadales (P=0.003) were correlated with higher CRP levels; higher abundance of class Mollicutes (0.024), family Prevotellaceae (P=0.030), phylum Tenericutes (P=0.024) were correlated with lower levels of CRP. No significant pleiotropy or heterogeneity was found in the results of sensitivity analysis, and no significant causality was found in reverse MR analysis. Conclusion This study highlighted associations within gut-kidney axis, and the causal relationships between GM and CKD, as well as GM and chronic systemic inflammation in CKD were also revealed. Meanwhile, we expanded specific causal gut microbiota through comprehensive searches. With further studies for causal gut microbiota, they may have the potential to be new biomarkers for targeted prevention of CKD and chronic systemic inflammation in CKD.